JQuery fundamentals LiveLessons (video training) - Dutson, Phil 1981- (Addison-Wesley Professional, 2012)
"JQuery Fundamentals LiveLessons covers the core jQuery library. This library gives you an easy to use solution that will enhance the functionality and use of your website. Each lesson in this video focuses on a particular portion of the jQuery library, and by the end viewers should be proficient in using jQuery, as well as writing their own plugins. Viewers will learn how to set up a development environment, including a web server, in both Windows and OSX; use a selector and refine the elements selected; move around the Document Object Model (DOM) tree to selected elements; manipulate the DOM; change attributes and styles; utilize Event handling; add animations and effects; load data remotely through various Ajax calls and actions; and finally, how to use jQuery plugins and how to create their own."--Resource description page.
Title from resource description page (viewed Apr. 9, 2013)
Keywords: JavaScript (Computer program language); Web site development; Web sites -- Design; JavaScript (Langage de programmation); Sites Web; Développement; Sites Web; Conception; Web sites; Design